Wedding Representation in Korean Drama (Semiotic Analysis in Drama “The World of The Married Couple”) - Rizqi Nur Amaliyah Putri; Aulia Rahmawati (JOSAR (Journal of Students Academic Research), 2023)
Its shows increase mindset and ideologic their audinces. There are so many point of views which can be taken from every tittle of drama. One of them that makes researcher’s interesting to be studied deeper is “the world of the married couple”. This korean drama is different from other because it tells not about romance but general life after married with cheating, divorcing, etc. Here, researcher studies about wedding representation which is showed by this drama and uses semiotic analysis by Roland Barthes qualitatively with connotation and denotation analysis, five reading codes (hermeneutic, proaretic, symbolic, semic, and gnonic) also myth/ideologic inside it. There are 47 corpus reasearches which’s inside them contain issues of confusianism wedding culture. Finally myth/ideologic which is deliverd is opposite connotation that hanges point of views to changes concept about marriage which believes in patiarcal culture like this to be applied mindfully and not forced and can be applied scientifically.